Ação de microemulsão incorporada com levamisol in vivo como imunomodulador em presença de Giardia lamblia - Mara Rosa Gil Hernandes (2015)
Giardiasis is one of the most common human parasitic infections worldwide, affecting hundreds of millions of people, particularly in developing countries. The Giardia lamblia (G. lamblia) is a protozoan parasite that the human gut. G. lamblia infections are more common in children, with a prevalence of approximately 20% in Brazil. Several defense mechanisms have been proposed to eliminate the infection by G. lamblia Among them the activity of phagocytes. On the other hand, treatment of giardiasis utilizes antiparasitics drugs therapy, but in 20% of the cases the treatment is ineffective, occurring often resistance and side effects. Thus, the purpose of enhance efficacy or reducing toxicity of the drugs, microemulsions present themselves as an alternative dosage form for placement interesting molecules with therapeutic activity. The use of these vehicles is a viable alternative to control the release of stimulus which modulate the immune system. Thus aim of this study was to evaluate the modulation of the functional activity of mononuclear phagocytes (MN) the blood of the microemulsion system levamisole hydrochloride in the presence of G. lamblia. A liquid microemulsion formulation incorporated with levamisole hydrochloride (mole) from Oletado sorbitan, polysorbate 80, 1-butanol, triglycerides of capric/caprylic acid and distilled water was used. The modulation of the functional activity of phagocytes MN for this formulation was evaluated by the release of superoxide, the phagocytic/microbicidal activity, apoptosis and intracellular calcium release. It was observed that the MN phagocytes treated with levamisole microemulsion incorporated with increased phagocytic activity indexes microbicides and induced apoptosis. These data show that the microemulsion is able to improve the therapeutic efficacy of levamisole, increasing the functional activity of these cells. Thus, Amele may be a suitable alternative for the efficient utilization of potential immunological treatment and applied to infection by G. lamblia and minimizing side effects.